Re-Oreintation of Nigerians Towards Mental Health: Its Counseling Implications - Bukoye Roseline Olufunke (European Scientific Journal, ESJ, 2017)
Mental health is a state of well-being which allows a better realisation of one's own potentials. With good mental health, individuals are able to cope productively with life situations. According to WHO (2002), hundreds of millions of people worldwide are affected by mental health problems. This led to their defection in terms of behavioural, neurological, physical, emotional, and substance use. It was discovered that about 36 million people worldwide are HIV positive, and about 20 million people have died from AIDS, tobacco, alcohol, amongst others. The use of hard drugs are discovered as potential addictive substance that have led to major health problems like heart diseases, stroke, cancer, liver diseases, fever, amongst others. Mental illness/problem occurs due to careless attitudes towards mental health education. Most middle and low income countries devote less than 1% of their health expenditure to mental health and mental health education thereby worsening the health condition of the citizens. This paper, therefore, sees it as point of urgency to re-orientate Nigerians towards mental health and its counseling implications. For its effectiveness, the roles of counseling cannot be over- emphasised. There is need for counsellors to inculcate into the public mental health skills, self-management skills, and self-descriptive culture through seminars and workshops. The Counsellor should bring to the awareness of the public information about their lifestyles regarding sleeping procedures, eating behaviour, nutrition, exercise, and stress management through enlightenment campaigns and medical programmes. Other recommendations include; the government in collaboration with the counsellors and NGOs should embark on comprehensive mental health problems preventive programmes. Also, mental health policies, legislation, community care giver facilities, and treatments for people with mental illness should be given proper attention.